2014
DOI: 10.1186/1472-6963-14-321
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public attitudes to and awareness of clinical practice guidelines: a systematic review with thematic and narrative syntheses

Abstract: BackgroundClinical practice guidelines are typically written for healthcare providers but there is increasing interest in producing versions for the public, patients and carers. The main objective of this review is to identify and synthesise evidence of the public’s attitudes towards clinical practice guidelines and evidence-based recommendations written for providers or the public, together with their awareness of guidelines.MethodsWe included quantitative and qualitative studies of any design reporting on pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 38 publications
4
78
0
Order By: Relevance
“…For health care professionals, CPG databases and portals overcome this challenge, and perhaps a similar website or portal of patient versions by topic may be useful for patients and the public. Our review of qualitative research about attitudes and beliefs about guidelines indicated that people do not necessarily trust information from guidelines [4]. While the majority of patient versions included logos of national and professional organisations which may convey credible sources, logos do not convey that these patient versions are providing recommendations that are based on a rigorous process which should be emphasised in these versions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…For health care professionals, CPG databases and portals overcome this challenge, and perhaps a similar website or portal of patient versions by topic may be useful for patients and the public. Our review of qualitative research about attitudes and beliefs about guidelines indicated that people do not necessarily trust information from guidelines [4]. While the majority of patient versions included logos of national and professional organisations which may convey credible sources, logos do not convey that these patient versions are providing recommendations that are based on a rigorous process which should be emphasised in these versions.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, materials for patient empowerment build upon patient education, and also include information to help people consider their own experiences, preferences and resources to inform decisions [3]. While building on the research for communicating research to patients is helpful, our recent systematic review of the literature about patient and public attitudes to CPGs found that there may be unique factors to consider when communicating guidelines [4]. Our review found that people may not always perceive guidelines positively.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In shared decision-making, information exchange is bi-directional (246), but guidelines are predominantly uni-directional, with information on the benefits and harms transferring from 132 clinician to patient (441). Primary care clinicians have called for improvements that foster patient-centred management of multiple conditions and strengthen the patient voice (33,67,250,308,309).…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%